2015
DOI: 10.1113/jphysiol.2014.286518
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial emission of reactive oxygen species and calpain activation are required for doxorubicin‐induced cardiac and skeletal muscle myopathy

Abstract: Key pointsr Although doxorubicin is a highly effective anti-tumour agent, the administration of this drug is associated with significant side effects, including contractile dysfunction and myopathy of both cardiac and skeletal muscles. The mechanism(s) responsible for doxorubicin-induced contractile dysfunction and myopathy in cardiac and skeletal muscles remains unclear.r In the present study, we report that increased mitochondrial oxidant production and calpain activation are major contributors to the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(180 citation statements)
references
References 60 publications
12
168
0
Order By: Relevance
“…Following doxorubicin administration, soleus mitochondrial NADH-and FADH 2 -supported respiratory capacity is diminished. These findings are consistent with our previous work and other groups demonstrating that doxorubicin causes skeletal muscle mitochondrial dysfunction in a time-dependent manner (12,17,26).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Following doxorubicin administration, soleus mitochondrial NADH-and FADH 2 -supported respiratory capacity is diminished. These findings are consistent with our previous work and other groups demonstrating that doxorubicin causes skeletal muscle mitochondrial dysfunction in a time-dependent manner (12,17,26).…”
Section: Discussionsupporting
confidence: 83%
“…Min et al (26) reported elevated H 2 O 2 emission in both PmFBs from cardiac and skeletal muscle following doxorubicin administration, along with elevated markers of protein oxidation. Elevated H 2 O 2 -emitting potential in skeletal muscle induced by doxorubicin is likely due to redox modifications within the matrix (e.g., the ETS, redox-buffering system) (12).…”
Section: E298 Cancer Chemotherapy and Mitochondrial Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anticancer treatments also have potent effects on mitochondrial function in the heart with doxorubicin-mediated cardiac toxicity in mice shown to be due, at least in part, to p53-mediated oxidative stress (114). Another study employed a novel mitochondrialtargeted antioxidant and a selective calpain inhibitor to demonstrate that doxorubicin-induced atrophy and dysfunction of skeletal and cardiac muscles involved increased mitochondrial reactive oxygen species production and calpain activation (73). These findings indicate that mitochondrial dysfunction caused by both cancer and its treatments contributes to the atrophy of skeletal and cardiac muscle, and therefore the mitochondria represents a promising therapeutic target for the treatment of skeletal and cardiac muscle cachexia in cancer.…”
Section: Pathogenesis Of Cardiac Atrophy In Cancer Cachexia: Protein mentioning
confidence: 99%